THE ROLE OF INTERNAL AUDIT IN EVALUATING ENVIRONMENTAL PERFORMANCE BY APPLICATION IN THE MINISTRY OF HEALTH / MEDICAL CITY DEPARTMENT - Researcher Fatima Adi Qassem; A.M.D., Saddam Kati Hashem; Assistant Professor Dr Saddam Catea Hashim Fatimah Oday Qasim (Scholars Digest Publishing, 2024)
This research aims to identify the importance of internal audit and the extent of its contribution to evaluating environmental performance when using performance evaluation indicators and addressing environmental problems in order to improve and preserve the environment and improve the performance of government units. The problem of the research was the failure of internal audit to carry out procedures. Environmental performance, and thus this deficiency is reflected in monitoring the implementation of environmental improvement requirements in government unitsThe research tools were based on a survey of the reality of the availability of internal environmental auditing requirements in the research sample and proposing an environmental audit program. The research reached a set of conclusions.This is the poor performance of the unitGovernmentalThe subject of research in the field of the environment is due to the lack of interest in auditing, monitoring and treating pollution, which relates to most aspects of the environment, and one of the most important recommendations isNecessity of useEnvironmental performance evaluation indicators to measure and track environmental activities and programs carried out by the unit in order to improve internal environmental audit procedures.
Keywords: Audit , internal audit , performance , evaluating environmental performance